KETERKAITAN USAHA KECIL SEKTOR PARIWISATA DENGAN SEKTOR-SEKTOR EKONOMI LAINNYA DI PROVINSI BALI: SUATU PENDEKATAN MODEL INPUT-OUTPUT - MADE ANTARA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2008)
Development in Bali Province Bali based on economic aspect with emphasis at agriculturalsector in wide meaning to continue of efforts to settle self sufficiency in food, development of tourismsector with character culture of Bali which is soul by Hinduism, and also small industrial sector andsmall industry which related to agricultural sector and tourism sector. Objective of the researchnamely: (1) to know forward and backward linkages of tourism small enterprise with the othereconomic sectors, (2) to know forward and backward dispersive power of tourism small enterprisewith other economic sectors. This research use approach of Input-Output Tourism Bali year 2000, assource of especial data and also data-processing method to answer the objective research.Result of research indicate that tourism small enterprise has forward and backward indirectlinkages are strongly that indicated by linkage coefficient bigger than one. Despitefully that tourismsmall enterprise have backward dispersive power high and forward dispersive power forwards lower,so that including potential sector to be developed, because can pull other sectors to increase itsoutputs or absorption of input generating demand pulling of raw material for production.Tourism small industry have potential and strategic role to be developed and also personate astrigger of economic growth. Therefore, small industries at this tourism sector better continue to bedeveloped and constructed, either through capital aid, training of management, and also aid accessmarket, so that powered progressively and professional.